DOP048 Vedolizumab levels during induction are associated with long-term clinical and endoscopic remission in patients with inflammatory bowel disease. (16th January 2018) - Yarur, A; Bruss, A; Fox, C; Beniwal-Patel, P; Patel, A; Berens, B; Naik, S; Stein, D
Abstract: Background: Cross-sectional serum vedolizumab (VDZ) levels (SVL) have been associated with disease activity in Crohn's disease (CD) or ulcerative colitis (UC) but the role of therapeutic drug monitoring (TDM) early in the course of therapy is unknown. The aim of this study was to assess the association of serum vedolizumab (VDZ) levels (SVL) during induction and remission in CD and UC after 52 weeks (52w) of therapy. We also sought to assess predictive variables associated with SVL through the first 22w of therapy. Methods: Prospective cohort study including patients with active UC and CD starting standard therapy with VDZ. Predictive variables included demographics, pre-infusion SVL measured using a validated drug-tolerant assay at weeks 2, 6, 14 and 22 (Anser® VDZ), C-reactive protein (CRP), albumin level, feacal calprotectin (FC), Harvey–Bradshaw index (HBI) in CD and Mayo Clinical Score (MCS) in UC, Simple endoscopic score-CD (SES-CD) in CD and Mayo endoscopic score (MES) in UC. Primary outcome was deep remission at 52W, defined as HBI<5 (in CD)/MCS<3 (in UC), and SES-CD≤2 (in CD) or MES≤1 (in UC). Secondary outcome was discontinuation of VDZ due to non-response. Results: Of the 53 patients in the study population, 28 (53%) had UC. Twenty-one (40%) achieved deep remission by week 52. These patients had higher SVL at weeks 2, 6, 14 and 22 of therapy vs. those that did not, but only the differences at Weeks 2 and 6 achieved statistical significance (Figure 1). Nineteen (36%) patients discontinued VDZ due to non-response. Differences between those that were and were not in deep remission at week 52 are shown in Table 1. Patients that started VDZ on combination therapy with an immunomodulator did not have significantly higher SVL at any time-point when compared with those who did not ( p > 0.05 for all). There was a positive, significant correlation between baseline albumin levels and SVL at week 6 (rho: 0.4, p = 0.003) and positive but not significant correlation and SVL at week 2 (rho: 0.2, p = 0.09). Furthermore, there was a significant negative correlation between baseline FC and SVL at week 2 (rho: −0.5, p < 0.001) and week 6 (rho: −0.33, p = 0.03). Conclusions: Vedolizumab levels at induction are associated with achievement of remission at 52w of therapy. While interventional studies are needed, the use of early TDM in patients on VDZ may improve outcomes.